Immune Infertility : Impact of Immune Reactions on Human Fertility - Krause, Walter K.H; Naz, Rajesh K. (Springer International Publishing : Imprint: Springer, 2017)
This book offers comprehensive coverage of both basic and clinical aspects of immune reactions responsible for infertility. It has four sections focusing on Sperm antigens, Antisperm antibodies (ASAs), Clinical impact of ASAs, and Immune contraception, and include contributions from leading experts in these fields. This new edition of the book offers a comprehensive update that reflects the very significant advances in reproductive immunology that have been achieved over the past five years, especially related to the sperm proteome, sperm-egg binding/fusion proteins, gene knockout studies, and immunocontraception. Reproductive immunology continues to be a fast-growing discipline in which new knowledge is emerging almost every day. Immune Infertility is a model source of vital and reliable information on the latest scientific developments in the field. It will be of value for clinicians, scientists, students, residents, and fellows working in reproductive biology, obstetrics and gynecology, and urology.
Keywords: Medicine.; Immunology.; Dermatology.; General practice (Medicine).; Gynecology.; Reproductive medicine.; Urology.; elektronické knihy; electronic books